Spectral features of biogenic calcium carbonates and implications for astrobiology. Issue 4 (10th September 2014) - Berg, B. L.; Ronholm, J.; Applin, D. M.; Mann, P.; Izawa, M.; Cloutis, E. A.; Whyte, L. G.
Abstract The ability to discriminate biogenic from abiogenic calcium carbonate (CaCO3) would be useful in the search for extant or extinct life, since CaCO3 can be produced by both biotic and abiotic processes on Earth. Bioprecipitated CaCO3 material was produced during the growth of heterotrophic microbial isolates on medium enriched with calcium acetate or calcium citrate. These biologically produced CaCO3, along with natural and synthetic non-biologically produced CaCO3 samples, were analysed by reflectance spectroscopy (0.35–2.5 μm), Raman spectroscopy (532 and 785 nm), and laser-induced fluorescence spectroscopy (365 and 405 nm excitation). Optimal instruments for the discrimination of biogenic from abiogenic CaCO3 were determined to be reflectance spectroscopy, and laser-induced fluorescence spectroscopy. Multiple absorption features in the visible light region occurred in reflectance spectra for most biogenic CaCO3 samples, which are likely due to organic pigments. Multiple fluorescence peaks occurred in emission spectra (405 nm excitation) of biogenic CaCO3 samples, which also are best attributed to the presence of organic compounds; however, further analyses must be performed in order to better determine the cause of these features to establish criteria for confirming the origin of a given CaCO3 sample. Raman spectroscopy was not useful for discrimination since any potential Raman peaks in spectra of biogenic carbonates collected by both the 532 and 785 nm lasers were overwhelmed by fluorescence. However, this also suggests that biogenic carbonates may be identified by the presence of this organic-associated fluorescence. No reliable spectroscopic differences in terms of parameters such as positions or widths of carbonate-associated absorption bands were found between the biogenic and abiogenic carbonate samples. These results indicate that the presence or absence of organic matter intimately associated with carbonate minerals is the only potentially useful spectral discriminator for the techniques that were examined, and that multiple spectroscopic techniques are capable of detecting the presence of associated organic materials. However, the presence or absence of intimately associated organic matter is not, in itself, an indicator of biogenicity.